Arquitetura e estrutura: o uso do concreto armado em Fortaleza - Diógenes, Beatriz Helena Nogueira (2001)
The structure is configured as an essential component of the architectural work. Recently, there has been an important evolution in the structural projects of buildings, provided by the use of new materials, application of modern techniques, in addition to the use of information technology, with reflections on the design of advanced design principles. This work aims to present the results of a research carried out on reinforced concrete structures, in which the consequent interferences in the architectural space are addressed and the use of the material in built works in the city of Fortaleza is appreciated. The study is divided into two parts. the first part deals with structures in general, their meaning and use in building, their importance in relation to architecture, as well as the close relationship between the structural solution and the architectural space. Considerations are also made about the reinforced concrete as a structural element, and about the emergence and diffusion of the material in Brazil and in the world, always trying to establish the interrelationships between structure and architecture. The second part, predominantly practical, consists of an analysis of the use of reinforced concrete in Fortaleza, made with the objective of verifying the ways of using the material in buildings already built or still in the execution phase. This analysis appears preceded by a brief history of the beginning and development of reinforced concrete techniques in the city. The research can confirm that reinforced concrete is the dominant material in the structures of buildings, and it was possible to verify that the city of Fortaleza has a high technological level with regard to the design and execution of reinforced concrete structures.